From Silence to Voice: Constitutionalizing Gender Parity and Political Inclusion in Indonesia’s Electoral Democracy - Budi Purwanto; Ngabowaji Daniel Nte; Muhammad Ikbal (ARTES LIBRES INSTITUTUM, 2025)
This study examines the constitutionalization of gender parity as a response to women’s persistent underrepresentation in Indonesia’s electoral democracy. The research objective is to explore how constitutional guarantees of equality have been translated into political practice, why the implementation of gender quotas has yielded limited outcomes, and how these dynamics intersect with broader socio-economic inequalities. Employing a normative legal research method combined with a comparative constitutional approach, the analysis draws on constitutional provisions, statutory law, and Constitutional Court jurisprudence, while situating Indonesia’s experience alongside global cases, particularly from Latin America, where gender parity has been constitutionally entrenched. The findings indicate that Indonesia’s constitutional architecture provides formal recognition of equality but remains trapped in what can be described as a constitutional poverty trap: rights exist in the text but are unrealized in practice. Political parties act as decisive gatekeepers, often circumventing quota requirements by relegating women to unelectable positions or nominating candidates without sufficient resources, while the financialization of electoral politics and entrenched patriarchal norms further obstruct women’s inclusion. Comparative evidence from countries such as Bolivia and Mexico demonstrates that embedding parity as a constitutional principle, coupled with judicial enforcement and socio-economic reforms, can yield transformative outcomes. The study concludes that breaking the cycle of exclusion requires strengthening constitutional jurisprudence, reforming political party laws, regulating campaign finance, and integrating socio economic rights into the gender parity discourse. By doing so, Indonesia can move from symbolic recognition to substantive realization, transforming constitutional commitments into lived political equality.